MR cholangiopancreatography : techniques, results, and clinical indications - Pavone, P; Passariello, R; Laghi, A; Catalano, C; Ferrucci, Joseph T (Springer, 1997)
Magnetic resonance cholangiography is a new noninvasive diagnostic technique for direct visualization of biliary ducts. It requires neither contrast medium nor biliary intervention. This book describes this technique in detail, listing present and potential indications as well as the differences that come from using different MR systems. Also presented in detail are the results in different clinical settings, which are discussed with reference to the illustrations.
Keywords: magnetická rezonanční tomografie; gastroenterologie; Cholangiography; radiologie, nukleární medicína a zobrazovací metody; Magnetic Resonance Imaging; cholangiografie